Construction site wastes (non-physical) categorization in Addis Ababa based on lean concept - Sahlu , Assay; Dinku, Abebe (Zede Journal of Ethiopian Engineers and Architects, 2023)
Waste in the construction industry has been the subject of several research projects around the world in recent years. One of the effective methods of wastage reduction is the application of lean approach to construction industry. Lean construction is a result of the introduction of a new form of production management. In general, project managers tend to conceptualize “waste” as physical construction waste only, but there are noticeable wastes in the construction processes which are named “non-value adding activities” by lean construction theory. In addition to stressing on the physical waste, lean thinking specifically pays lots of attentions to the waste produced over a construction process. Waiting time, non-value adding (NVA) works and material transportations are categorized in this group. This article is focused on categorizing construction site activities based on lean concept on selected six construction sites. These activities include rebar work for slab, formwork for column and concrete cast for slab. Video data collection method was mainly used to conduct the study. Video data collection required to be entered into spreadsheets so that the necessary tabular results could be generated. The results of the case studies showed that, a significant portion of crew working hours was spent on NVA activities. Among the NVA activities, waiting time took the largest share, indicating interruption of flow in the work process. The results of the study further pointed out that, time spent on non-value adding but required activities (NVAR), like temporary work and supporting activities can also be minimized by using better technologies (materials and equipment).